C# 2.0 practical guide for programmers - Champlain, Michel de.; Patrick, Brian G. (Amsterdam ; Boston : Elsevier, 2005)
You dont need coddling; you dont need to be told what you already know. What you need is a book that uses your experience as a Java or C++ programmer to give you a leg up into the challenges and rewards of C#. And this Practical Guide is precisely what youre after. Written by a team that boasts extensive experience teaching C# to professionals, this book provides a practical, efficient explanation of the language itself, covering basic to advanced features and calling out all thats new in 2.0. Its instruction is always firmly situated within the context of the .NET framework and bolstered by code examples, key lessons in object-oriented programming, and installments of a realistic application programming tutorial. Concise and incisive, this is the best way to master the worlds fastest-growing and most marketable programming language. Features * Provides a carefully focused explanation of every aspect of the C# language, including entire chapters on the unified type system, advanced types, collections, generics, reflection and attributes. * Highlights all features new to the latest version of C# and organizes its presentation of C# according to the key principles of object-oriented programming and the .NET framework. * Using end-of-chapter exercises, incrementally develops a cohesive application programming tutorial. * Includes an easy-to-use appendix on the grammatical rules of C# and provides downloadable example code via the companion website. * Provides a carefully focused explanation of every aspect of the C# language, including entire chapters on the unified type system, advanced types, collections, generics, reflection and attributes. * Highlights all features new to the latest version of C# and organizes its presentation of C# according to the key principles of object-oriented programming and the .NET framework. * Using end-of-chapter exercises, incrementally develops a cohesive application programming tutorial. * Includes an easy-to-use appendix on the grammatical rules of C# and provides downloadable example code via the companion website.
Introducing C# and .NET -- Classes, objects, and namespaces -- Class members and class reuse -- Unified type system -- Operators, assignments, and expressions -- Statements and exceptions -- Advanced types, polymorphism, and accessors -- Collections and generics -- Resource disposal, input/output, and threads -- Reflection and attributes.
Includes bibliographical references (p. 243-244) and index.
Keywords: C# (Computer program language).; Electronic books